2016
DOI: 10.18805/ijar.11458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hibiscus seed-based diet on chemical composition,carcass characteristics and meat quality traits of cattle

Abstract: This study investigated the effects of Hibiscus (Hibiscus sabdariffa L.) seeds inclusion in diet of cattle. Fifty-five Sudan Baggara bulls were selected and divided into five treatment groups, and fed iso-caloric and iso-nitrogenous experimental diets where groundnut cake was the source of protein in the control diet (0% Hibiscus seeds), while in the other experimental diets, Hibiscus seeds replaced groundnut at a rate of: 25, 50, 75, and 100%. The crude protein was significantly lower in the 100% group than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…This might be due to different nature of the leaves plant, location and time of harvesting. The WAC for the seeds of Karkade were similar with WAC of Karkade seeds reported by Suliman et al (2017) (2.95 g/g). The result indicated that the seeds of Karkade flour contain (Omueti et al, 2009).…”
Section: Functional Propertiessupporting
confidence: 87%
“…This might be due to different nature of the leaves plant, location and time of harvesting. The WAC for the seeds of Karkade were similar with WAC of Karkade seeds reported by Suliman et al (2017) (2.95 g/g). The result indicated that the seeds of Karkade flour contain (Omueti et al, 2009).…”
Section: Functional Propertiessupporting
confidence: 87%
“…The ash content was significantly higher in the Harri breed (1.11%) than the Awassi and Najdi breeds, which had similar ash content (1.07%). In general, the chemical composition of meat is affected by numerous factors, including diet, carcass weight, and breed ( 10 , 11 , 13 , 15 , 17 27 ). The moisture content of the three sheep breeds was in the range reported by Abdullah and Qudsieh ( 28 ) for Awassi sheep.…”
Section: Resultsmentioning
confidence: 99%
“…The meat sample was placed in an electric commercial stainless-steel grilling oven and cooked at 200 • C to an internal temperature of 70 • C. The internal temperature of the sample was monitored by inserting a thermocouple probe (Ecoscan Temp JKT, Eutech Instruments, Pte Ltd., Keppel Bay, HarbourFront, Singapore) into the center of each steak. The category scaling method was used to categorize the meat samples on an 8-point category scale following Suliman et al (11,12). A panel of eight trained panelists assessed the cooked meat samples for flavor, tenderness and juiciness.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Table 1 shows the chemical composition of HS seeds reported by different authors, and on average, HS seeds contain: crude protein (CP), 27.9 ± 10 g/100 g of dry matter (DM); fat, 18.8 ± 8.6 g/100 g DM; crude fiber (CF), 16.8 ± 11.1 g/100 DM; and ashes, 5.86 ± 3.2 g/100 DM [43,47]. The phenolic and antioxidant activities of HS seeds have been previously assayed, and results were similar or better than those in calyxes [46].…”
Section: Hibiscus Sabdariffa L By-productsmentioning
confidence: 99%